(untitled) (Northern International Medical College Journal, 2025)
Background: Pleural effusion is a frequent cause of respiratory morbidity in children, with variable etiology and outcomes depending on geography, vaccination status, and underlying diseases and timely management. Methods: This prospective observational study was conducted in the department of Respiratory Medicine of Bangladesh Shishu Hospital and Institute, enrolling 511 consecutive children diagnosed radiologically as pleural effusion between January 2022 and June 2024. Clinical features, imaging findings and pleural fluid analyses including cytology, biochemistry, microbiology, Gene Xpert, adenosine deaminase (ADA), lactate dehydrogenase (LDH) and immunochromatographic test (ICT) for Streptococcus pneumoniae were performed for all patients. Data was analyzed descriptively using SPSS v24. Results: Among the children enrolled total 218 (42.7%) were aged 5–<10 years. All children below 10 years (n=343) were fully immunized with PCV-10 as per EPI schedule of Bangladesh. Empyema was found in 112 (21.9%) and tubercular pleural effusion in 103 (20.2%) cases. Among bacterial infectious etiologies were found Streptococcus pneumoniae the leading isolate (49 cases/42.1%) followed by Pseudomonas aeruginosa (17) and Klebsiella pneumoniae (10). Multi Drug Resistant S. pneumoniae was detected in 13 (26.5%) cases. Two (0.4%) children had co-infection of Mycobacterium tuberculosis and S. pneumoniae. The remaining cases included nonspecific exudative effusions. A total of 472 (92.3%) children improved with appropriate management including antibiotics, chest tube drainage, and antitubercular therapy. Thirty-nine (7.7%) had persistent or loculated effusions requiring surgical intervention and prolonged hospitalization. Conclusion: Despite widespread coverage of PCV-10 vaccination, S. pneumoniae remained the main pathogen and emergence of MDR Pneumococcus is alarming. It might be highlights the possible serotype replacement and vaccine escape. Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 712-715